2000
DOI: 10.1007/pl00008867
|View full text |Cite
|
Sign up to set email alerts
|

A positive association between oviposition and fruit set: female choice or manipulation?

Abstract: The relationship between where a female chooses to oviposit and her larvae's performance at those sites is critical to both the ecology and evolution of plant-insect interactions. For predispersal seed predators that do not themselves pollinate their host and whose larvae are sessile, females must be able to predict which flowers will ultimately be pollinated and set fruit, or be able to manipulate flowers in some way to ensure they set fruit. Otherwise, their offspring will perish. Here we describe the result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 63 publications
0
21
0
1
Order By: Relevance
“…Selective abscission of fruits damaged by insects has been reported for many plant species (Janzen 1971;reviewed in Sallabanks and Courtney 1992). A survey of 15 studies representing insects from the orders Coleoptera, Diptera, Hemiptera, and Lepidoptera showed that insects ovipositing or feeding on flowers increased the rate of floral abscission, although at least one study has shown that insect oviposition behavior can increase fruit retention (Brody and Morita 2000). Five of the 15 studies specifically tested how insects caused floral abscission.…”
Section: Discussionmentioning
confidence: 98%
“…Selective abscission of fruits damaged by insects has been reported for many plant species (Janzen 1971;reviewed in Sallabanks and Courtney 1992). A survey of 15 studies representing insects from the orders Coleoptera, Diptera, Hemiptera, and Lepidoptera showed that insects ovipositing or feeding on flowers increased the rate of floral abscission, although at least one study has shown that insect oviposition behavior can increase fruit retention (Brody and Morita 2000). Five of the 15 studies specifically tested how insects caused floral abscission.…”
Section: Discussionmentioning
confidence: 98%
“…Although some plants were still flowering, flowers produced so late in the season were unlikely to be pollinated and set seed. Therefore the few remaining flowers were counted as unsuccessful (per Brody and Morita 2000).…”
Section: Experimental Designmentioning
confidence: 99%
“…The positive eVect of Hylemya on the probability of a fruit setting seed has been previously documented and tested (Brody 1992b;Brody and Waser 1995;Brody and Morita 2000). Although the physiological mechanism remains a mystery, female Hylemya-by virtue of some subtle manipulation of the Xowers on which they oviposit and not through choice of fertilized Xowersenhance fruit set of I. aggregata Xowers (Brody and Morita 2000). Fruit and seed predation and herbivory on plants and Xowers that are more likely to set fruit has been shown in other systems as well (Herrera 2000;Cariveau et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, these seed predators can greatly reduce total seed production (Juenger and Bergelson 1998). Unlike other plants which may abscise damaged Xowers or selectively abort damaged fruits (Pellmyr and Huth 1994), I. aggregata does not abort fruits with Hylemya larvae and, in fact, the probability of fruit set is higher for Xowers on which females oviposit than on other Xowers of the same plant (see below, and Brody and Morita 2000).…”
Section: Study Systemmentioning
confidence: 95%